Unmasking the internet: investigating UK women’s digital entrepreneurship through intersectionality - Martinez Dy, Angela Carmina (2015)
This thesis investigates the experiences of women digital entrepreneurs in the United Kingdom from an intersectional cyberfeminist perspective. Informed by feminist theories of technology and critical entrepreneurship scholarship, it challenges mainstream discourse on digital entrepreneurship with the argument that, similar to traditional (offline) entrepreneurship, online or digital entrepreneurship is deeply embedded in the social world. It draws upon intersectional feminist theory that conceptualises the social world as composed of intersecting hierarchies of race, class, and gender, in which individuals and groups are positioned in dynamic yet durable ways, and by which they are affected simultaneously. This positionality is found to be tied to unequal resource distribution, and for this reason, holds important implications when mapped to extant entrepreneurship theory. The thesis also provides interdisciplinary evidence for the continued coding of Internet technology as predominantly white and male, and for the online environment itself as a stratified and unequal space, countering public discourse that portrays it as a neutral and meritocratic ‘great equaliser.’